1995
DOI: 10.1080/00071669508417822
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in immunoreactive inhibin and FSH in plasma of chickens from hatch to sexual maturity

Abstract: 1. The relationship between immunoreactive inhibin and follicle-stimulating hormone (FSH) was studied in male and female chickens from hatch to sexual maturity. Plasma inhibin was estimated by a heterologous radioimmunoassay validated for use in the chicken. FSH was measured by a recently developed homologous radioimmunoassay. 2. In a cross-sectional study, blood samples and gonads were collected from chickens of both sexes at 1, 3, 5, 7, 14, 21 and 28 d after hatching and subsequently at 14-day intervals unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 39 publications
6
13
0
Order By: Relevance
“…In the present study, the inhibin α and inhibin/activin βA and βB subunits were expressed in the granulosa cells of all follicles during different stages of development from 1 to 7 weeks after hatching, indicating that granulosa cells may secrete dimeric and bioactive inhibins during the follicular development of Japanese quails. Immunolocalization of the inhibin/activin subunits in the granulosa cells of the quail ovary is in agreement with previous studies showing that the granulosa cells of chicken [18,19] and duck [30,31] ovaries are the major source of inhibin. In hens, the greatest amount of mRNA expression for the inhibin/activin βA subunit is found in the F1 follicle, while the inhibin α subunit is expressed more abundantly than the inhibin βA subunit in large preovulatory follicles.…”
Section: Sedqyar Et Al 56supporting
confidence: 79%
See 3 more Smart Citations
“…In the present study, the inhibin α and inhibin/activin βA and βB subunits were expressed in the granulosa cells of all follicles during different stages of development from 1 to 7 weeks after hatching, indicating that granulosa cells may secrete dimeric and bioactive inhibins during the follicular development of Japanese quails. Immunolocalization of the inhibin/activin subunits in the granulosa cells of the quail ovary is in agreement with previous studies showing that the granulosa cells of chicken [18,19] and duck [30,31] ovaries are the major source of inhibin. In hens, the greatest amount of mRNA expression for the inhibin/activin βA subunit is found in the F1 follicle, while the inhibin α subunit is expressed more abundantly than the inhibin βA subunit in large preovulatory follicles.…”
Section: Sedqyar Et Al 56supporting
confidence: 79%
“…Previous studies in female chickens have shown that inhibins are involved in regulation of their reproductive function [18,19]. Ir-inhibins in plasma have been shown to increase during sexual maturation [19], and it has been reported that the ir-inhibin content of granulosa cells and secretion into culture medium is correlated with the plasma levels [32]. Yang et al [31] reported that the rise in ir-inhibin is correlated with age at sexual maturity in female ducks, while a progressive increase in steroid hormones may be consistent with a progressive increase in the steroidogenic processes of the ovary.…”
Section: Sedqyar Et Al 56mentioning
confidence: 99%
See 2 more Smart Citations
“…Culler and Negro-Vilar [42] reported a negative relationship between FSH and inhibin in the postnatal rat. Also, the relationship between pituitary gonadotropins and gonadal inhibin has been characterized from hatching to maturity in chickens [43,44]. Both studies found a negative relationship between inhibin and FSH in female chickens that appeared to become functional at sexual maturity.…”
Section: Discussionmentioning
confidence: 97%